BIODIVERSITY AND LENGTH FREQUENCIES OF SHARKS CAUGHT IN THE INDIAN OCEAN - Dharmadi, -; Sumadhiharga, K.; Fahmi, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
Study on biodiversity and size structure of sharks in the Indian Ocean was conducted at several landing sites and fish markets, i.e. Pelabuhanratu (West Java), Cilacap (Central Java), Kedonganan (Bali) and Tanjung Luar (East Lombok ). Field observation was done from April 2001 to March 2006. The results showed that there were 86 species of sharks belonging to 16 families in the Indian Ocean. The sharks were dominated by family of Carcharhinidae and Squalidae with 24 and 23 species, respectively. A high diversity of sharks was found at Kedonganan-Bali (49 species), at Tanjung Luar (47 species), at Cilacap (32 species) and at Pelabuhanratu (27 species). Size of sharks landed at those landing sites varied in length, the length of Carcharhinus amblyrhynchos was between 90 cm and 170 cm TL, C. sorrah (55-155 cm), C. obscurus (205-295 cm) and P glauca was caught at length between 205-300 cm.